Pilot Study of an Internet-Based, Simulated Teachable Moment for Smoking Cessation. (September 2019) - May, Robin; Walker, Frances; de Burgh, Simon; Bartrop, Roger; Tofler, Geoffrey H
Abstract: Introduction: The internet has the potential to overcome geographic limitations for smoking cessation interventions, but further telehealth-based studies of utility are required. Aims: To investigate the efficacy of an internet-based version of a quit smoking approach using a personalised video to create a simulated teachable moment. Methods: Smokers within Australia were recruited through a dedicated website. After consent, eligible subjects, aged ≥30 years with a non-smoking partner, uploaded pictures of themselves, their partner and family, to be inserted into a video depicting the subject having a heart attack due to smoking, with consequences to them and their family. Nicotine replacement therapy (NRT) began prior to the quit attempt. The video was shown during two videoconference counselling sessions, with follow-up phone calls and text messaging support. Smoking status at 6 months by self-report (primary endpoint) was verified by partner/proxy and salivary cotinine (NicAlert™). Results/Findings: Seventy seven smokers were screened, of whom 50 were eligible, and 17 of these (34%) were enrolled; 11 men and 6 women, aged 41.5 ± 6.9 years, daily cigarette consumption 20.8 ± 8.9, Heaviness of Smoking Index score 3.7 ± 1.7. Participants reported feeling personally involved with the video (5.9 ± 1.1), which felt real (5.8 ± 1.1) and emotionally moving (5.6 ± 1.5) [7-point Likert Scale]. A similar video response was reported by the four participants (24%), who due to bandwidth limitations, watched the video after the counselling session instead of during it. Non-smoking rates at 6 months were 65% (11/17) by self-report with proxy confirmation, and 47% (8/17) by self-report with biologic confirmation. Three non-smokers by self-report could not provide a valid NicAlert™ result due to current NRT use. One participant who by self-report smoked once in the prior 14-days was assessed as a non-smoker by both proxy and NicAlert™. Conclusions: This pilot study demonstrates efficacy for an internet-based version of a quit smoking program based on creating a simulated teachable moment. The findings provide support for further research into this technique, with the internet enabling greater reach than face-to-face.